2022
DOI: 10.46843/jiecr.v3i4.300
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Intentions for Engineering Students: Does Entrepreneurship Education and Family Environment Matter?

Abstract: This research aims to analyze the influence of entrepreneurship education and family environment on engineering students' entrepreneurial intentions within higher education. This examination method used was associative causal research. The research methodology is based on statistics using multiple regression analysis. This research was conducted on undergraduate students (S1) in the 2020 entry year at the Faculty of Engineering, Universitas Negeri Padang, which consists of 10 different undergraduate study prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 73 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…In contrast, Qazi et al (2022) showed family support successfully moderating the relationship between the TPB variables and entrepreneurial intention among the women of Karachi, Pakistan. Samala et al (2022) found a positive significant impact of entrepreneurship education and family support on the entrepreneurial intention of engineering students.…”
Section: Review Of Literaturementioning
confidence: 90%
“…In contrast, Qazi et al (2022) showed family support successfully moderating the relationship between the TPB variables and entrepreneurial intention among the women of Karachi, Pakistan. Samala et al (2022) found a positive significant impact of entrepreneurship education and family support on the entrepreneurial intention of engineering students.…”
Section: Review Of Literaturementioning
confidence: 90%
“…In practice, if schools are to instill entrepreneurial values in students, there are several things that can be done, including 1) Improving the curriculum; 2) Increasing the role of schools in preparing businesspersons; 3) Improving the organization of the learning process; and 4) Encouraging self-improvement of teachers and, 5) Implementation of entrepreneurship education (Mulyani, 2021). Becoming an entrepreneur requires expertise to identify and understand all possibilities, gather the resources needed, and acting by taking advantage of existing opportunities to create a new businesses and creating business fields (Samala et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…If the education of entrepreneurship develops rapidly, it will have an impact on improving individuals' financial situation and improving the community's economy. http://ijlter.org/index.php/ijlter Researchers have examined the reasons why people's motivation to be entrepreneurs tends to be low (Samala et al, 2022). Research has found that success in entrepreneurship is influenced by various factors, one of which is entrepreneurship education (Lawal & Ojodu, 2022).…”
Section: Introductionmentioning
confidence: 99%